Perhitungan Kehilangan Batubara Pada Kegiatan Penimbangan Sampai Tongkang di PT Multi Harapan Utama Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Ilma Nurjanah; Agus Winarno; Henny Magdalena; Windhu Nugroho (ReTII, 2023)
The research was conducted at the stockROM owned by PT Multi Harapan Utama (PT MHU) which is managed by PT Mitra Terminal Kaltim. In the process of receiving to shipping coal, factors that cannot be avoided. The amount of coal loss from weighing to barge in May was 1,955 tons with factors that caused the loss, namely in the process of weighing, transporting, stacking, and crushing coal and loading on barges, taking test samples and operator negligence. Referring to the reference coal price of the Ministry of Energy and Resources (ESDM) in May 2023 PT MHU has the potential to experience a loss of Rp. 5.251.062.510.